Proposta de avaliação do Programa Nacional de Alimentação Escolar para municípios no estado do Rio de Janeiro - Carvalho, Camila Maranha Paes de (DEMETRA: Alimentação, Nutrição & Saúde, 2013)
The National School Diet Program (PNAE - Programa Nacional de Alimentação Escolar) stands out, in the food and nutrition policies of Brazil, for its range, intersectoral characteristics, and outline, aligned with the sectors of ​​food, nutrition, and public health. However, the theoretical framework related to its assessment is still poorly consolidated, especially in a local basis. The aim of this study was to develop an assessment proposal of PNAE for the cities located in the State of Rio de Janeiro (RJ) that have their own diet service. The work was divided into the following steps: bibliographic survey of research studies and assessment indicators of PNAE, development of graphical representations of the operational system of PNAE and of a preliminary assessment proposal, review of the list of assessment indicators of the Program and graphical representations, after inquiring the individuals involved in its implementation and experts on the subject, development of instruments for data collection, application of this list of indicators in a city of RJ; review of indicators as an experience of its application, and creation of a final assessment proposal. As a product, we present a group composed of 87 indicators, divided into six dimensions of assessment: management, promotion of healthy diet, local development, qualification of individuals, social control and participation, and point of view of social individuals. Of these indicators, 19 are qualitative and intend to subsidize research on necessary improvements to the program. The final representation of this assessment intends to use a filled radar chart, where each axis represents one of the assessment dimensions. Other outputs arising from this project are questionnaires to collect data from different key informants and conceptual maps of the program's operation with the identification of the proposed indicators.